Bioaccumulation of heavy metals in Capoeta tinca fish and health risk assessment - Demir, Tuğba; Mutlu, Ekrem; Gültepe, Necdet (Universidad del Zulia, 2024)
The This study evaluates the potential human health risks associated with five heavy metals (Zn, Pb, Cu, Cd, and Cr) in Capoeta tinca fish. It assesses the heavy metal burden in the muscle, gill, and liver tissues of C. tinca, and estimates the potential health risks for consumers by employing estimated daily intake (EDI) and standard hazard ratios (THQ) related to heavy metal consumption. Fish and water samples were taken from three different Regions as Sincan Brook (Sivas–Hafik), Habeş Brook (Sivas–Zara), and Tozanlı Brook (Sivas–Hafik), Turkey. The heavy metal concentrations in the brook water were found to be higher than the established safe for safety threshold in all the sampling points. Besides that, the values were observed to be lower than the allowed limits. Considering the fish tissues, the Pb, Cd, and Cr concentrations were found to be higher than the safe limits predicted by WHO. The findings indicate that the liver of C. tinca fish exhibited the highest accumulation of heavy metals across all sampling areas. The highest heavy metal concentrations found in fish muscles were found to be (Cu) 2.51 ± 0.91 μg·g-1, (Cr) 0.45 ± 0.03 μg·g-1, (Cd) 0.88 ± 0.04 μg·g-1, (Pb) 2.04 ± 0.03 μg·g-1, and (Zn) 13.12 ± 1.08 μg·g-1. The descending order of heavy metal accumulation in gills was found to be Zn > Cu >Pb > Cd > Cr. Moreover, for each heavy metal, the Bio–concentration factor (BCF) index, Acceptable Daily Intake, EDI, and THQ (<1) values were found to be lower than the limits set in the international standards, indicating that no elements posing a threat to public health were encountered, thus not posing a short–term risk.
Keywords: SF191-275; Veterinary medicine; risk assessment; fish quality; heavy metal; human health; Water quality; SF600-1100; Cattle; 6. Clean water; 3. Good health; 14. Life underwater